Mining through pandemic crisis: a systematic review of the impacts of COVID-19 management strategies on mining industries in West Africa and Western Australia - Esther Ayaaba; Kwadwo Adusei-Asante; Victor Fannam Nunfam; Krassi Rumchev; Samuel Kofi Amponsah (Critical Public Health)
The mining sector plays a crucial role in the economies of West Africa and Western Australia, contributing to GDP, employment, and foreign exchange earnings. However, the sector also faces environmental, social, and health challenges, including land and water degradation, human rights violations, and occupational hazards. The COVID-19 pandemic worsened these challenges, affecting aspects of the mining industry. This systematic review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for literature search and selection. PubMed and Google Scholar were searched for relevant articles published from 2019 to 2023. Inclusion criteria encompassed studies focusing on COVID-19 management strategies in West Africa and Western Australia mining sectors. Mining industries in both regions adopted a spectrum of strategies. These included lockdowns and movement restrictions, extensive testing and contact tracing, quarantine protocols, stringent health and safety measures, support for vulnerable artisanal miners, technology integration to reduce human interaction, flexible work arrangements, and mental health support. Some companies diversified their supply chains, and community engagement programmes aimed to inform and support local populations. However, these strategies often led to disruptions, work stoppages, and reduced production. Lockdowns affected mining community mobility and COVID-19 cases among miners. Mental health concerns arose, particularly in Western Australia, due to isolation measures and job insecurity. The COVID-19 pandemic had profound effects on mining industries in both regions. We have provided insights for future research and industry practices, emphasising the necessity of resilient strategies to protect both well-being and economic stability during pandemics.